Effect of Storage Temperature on Ram Seminal Plasma and Its Subsequent Use as Epididymal Tail Sperm Recovery buffer - Singh, Pawan Preet; Dar, Rameez Ali; Lone, Farooz Ahmad; Bhat, Ghulam Rasool; Yousuf, Nahida; Nisa, Masrat un (The Indian Journal of Animal Reproduction, 2024)
The study was undertaken to assess the effect of storage temperature of ram seminal plasma on its use as recovery and activation buffer for epididymal tail sperm. Five healthy cross bred rams were selected for semen collection maintained at Mountain Research Centre for Sheep and Goats, FVSc & AH, SKUAST-K. Semen was collected by artificial vagina method. Seminal plasma was harvested by double centrifugation method from the semen samples. Recovered seminal plasma was stored at two different temperatures i.e., 4°C and -20°C. Degree of ram epididymal tail sperm activation using homologous seminal plasma stored at 4°C and -20°C was investigated. The spermatozoa recovered in both types of seminal plasma were cold stored separately at 4°C for 72 hours. All the samples were evaluated after every 24 hours for spermatozoa quality. The percentage of sperm motility, viability and HOST reacted populations were significantly higher (p<0.05) in seminal plasma stored at 4°C than the seminal plasma stored at -20°C at all the time points of cold storage. Moreover, MDA level of seminal plasma stored at 4°C was significantly (p<0.05) lower than the seminal plasma stored at -20°C. In conclusion, seminal plasma harvested for epididymal tail sperm recovery may be stored at 4°C before its subsequent use as epididymal tail sperm recovery and activation buffer. However further studies are required to determine the shelf life of seminal plasma stored at 4°C.